Corticosteroids for pediatric septic shock patients - Irene Yuniar; Vembricha Nindya Manusita; Sonya Leonardy Low (Paediatrica Indonesiana, 2019)
Background Septic shock remains a major cause of mortality and admission to the pediatric intensive care unit (PICU) in children. Management includes adequate fluid resuscitation, followed by catecholamine infusion, if needed. Corticosteroid therapy is advised for catecholamine-refractory shock, although this practice is controversial, as it was not beneficial in other studies. Objective To assess corticosteroid use in pediatric septic shock patients in Cipto Mangunkusumo Hospital. Methods This cross-sectional study included all patients aged 1 month-18 years with a diagnosis of septic shock during the study period of January 2014 to July 2018 admitted in PICU Dr. Cipto Mangunkuskumo Hospital, Jakarta. Data obtained from medical records were, age, sex, immunology status, port dâ€™entrÃ©e of sepsis, inotropic and vasopressor usage, mechanical ventilation, corticosteroid type, hospital length of stay (LOS), and mortality outcome. Results Of 217 children with septic shock, 12 patients (5.5%) received corticosteroid therapy. The most common corticosteroid given was hydrocortisone (80%), with a 2 mg/kg BW loading dose, followed by a continuous infusion dose of 2-50 mg/kg BW/day. Almost all patients (11/12) received corticosteroid therapy until they died. Median duration of corticosteroid use was 2 (range 1-7) days, median number of inotropes and vasopressors used was 3 (range 2-4) agents, median LOS was 3 (range 1-9) days, and mortality rate was 100%. Conclusion A small proportion of pediatric septic shock patients received corticosteroid therapy. Their mortality rate was 100%. Further clinical study is needed to evaluate the benefit of corticosteroid therapy in pediatric septic shock patients.